First Case of Cancrum Oris (Noma) in an HIV-Positive Patient in Bulgaria - Grozdeva R. (Sciendo, 2020)
We present a case of a necrotising disease of the orofacial tissues, the so-called noma, in a female patient with AIDS in a stage of severe immune deficiency. To our knowledge, this is the first time a case like that has been reported in Bulgaria. The patient received an antibiotic course of treatment with a triple combination to good effect on the inflammatory process, and began also HAART. Within 3 weeks, the patient’s general condition improved. However, despite the treatment, a demarcation line was formed, and a defect on the lower lip occurred. Noma is a manifestation of severe immune deficiency with lasting adverse consequences for the patient: severe deformation of the maxilo-facial region and functional impairment (i.e. difficulties eating and speaking, and salivary leak).